Towards take‐all control: a C‐21β oxidase required for acylation of triterpene defence compounds in oat. Issue 3 (8th October 2018) - Leveau, Aymeric; Reed, James; Qiao, Xue; Stephenson, Michael J.; Mugford, Sam T.; Melton, Rachel E.; Rant, Jenni C.; Vickerstaff, Robert; Langdon, Tim; Osbourn, Anne
Summary: Oats produce avenacins, antifungal triterpenes that are synthesized in the roots and provide protection against take‐all and other soilborne diseases. Avenacins are acylated at the carbon‐21 position of the triterpene scaffold, a modification critical for antifungal activity. We have previously characterized several steps in the avenacin pathway, including those required for acylation. However, transfer of the acyl group to the scaffold requires the C‐21β position to be oxidized first, by an as yet uncharacterized enzyme. We mined oat transcriptome data to identify candidate cytochrome P450 enzymes that may catalyse C‐21β oxidation. Candidates were screened for activity by transient expression in Nicotiana benthamiana . We identified a cytochrome P450 enzyme AsCYP72A475 as a triterpene C‐21β hydroxylase, and showed that expression of this enzyme together with early pathway steps yields C‐21β oxidized avenacin intermediates. We further demonstrate that AsCYP72A475 is synonymous with Sad6, a previously uncharacterized locus required for avenacin biosynthesis. sad6 mutants are compromised in avenacin acylation and have enhanced disease susceptibility. The discovery of AsCYP72A475 represents an important advance in the understanding of triterpene biosynthesis and paves the way for engineering the avenacin pathway into wheat and other cereals for control of take‐all and other diseases.